Prospective characterization of protracted bacterial bronchitis in children - Wurzel, Danielle F; Marchant, Julie M; Yerkovich, Stephanie T; Upham, John W; Mackay, Ian M; Masters, I Brent; Chang, Anne B (Chest, 2014)
Prior studies on protracted bacterial bronchitis (PBB) in children have been retrospective or based on small cohorts. As PBB shares common features with other pediatric conditions, further characterization is needed to improve diagnostic accuracy among clinicians. In this study, we aim to further delineate the clinical and laboratory features of PBB in a larger cohort, with a specific focus on concurrent viral detection. Children with and without PBB (control subjects) undergoing flexible bronchoscopy were prospectively recruited. Basic immune function testing and lymphocyte subset analyses were performed. BAL specimens were processed for cellularity and microbiology. Viruses were identified using polymerase chain reaction (PCR) and bacteria were identified via culture. The median age of the 104 children (69% male) with PBB was 19 months (interquartile range [IQR], 12-30 mo). Compared with control subjects, children with PBB were more likely to have attended childcare (OR, 8.43; 95% CI, 2.34-30.46). High rates of wheeze were present in both groups, and tracheobronchomalacia was common. Children with PBB had significantly elevated percentages of neutrophils in the lower airways compared with control subjects, and adenovirus was more likely to be detected in BAL specimens in those with PBB (OR, 6.69; 95% CI, 1.50-29.80). Median CD56 and CD16 natural killer (NK) cell levels in blood were elevated for age in children with PBB (0.7 × 109/L; IQR, 0.5-0.9 cells/L). Children with PBB are, typically, very young boys with prolonged wet cough and parent-reported wheeze who have attended childcare. Coupled with elevated NK-cell levels, the association between adenovirus and PBB suggests a likely role of viruses in PBB pathogenesis.